Maxims violations in literary work - Widya Hanum Sari Pertiwi (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2013)
This study was qualitative research action that focuses to find out the flouting of Gricean maxims and the functions of the flouting in the tales which are included in collection of children literature entitled My Giant Treasury of Stories and Rhymes. The objective of the study is generally to identify the violation of maxims of quantity, quality, relevance, and manner in the data sources and also to analyze the use of the flouting in the tales which are included in the book. Qualitative design using categorizing strategies, specifically coding strategy, was applied. Thus, the researcher as the instrument in this investigation was selecting the tales, reading them, and gathering every item which reflects the violation of Gricean maxims based on some conditions of flouting maxims. On the basis of the data analysis, it was found that the some utterances in the tales, both narration and conversation, flouting the four maxims of conversation, namely maxim of quality, maxim of quantity, maxim of relevance, and maxim of manner. The researcher has also found that the flouting of maxims has one basic function that is to encourage the readers’ imagination toward the tales. This one basic function is developed by six others functions: (1) generating specific situation, (2) developing the plot, (3) enlivening the characters’ utterance, (4) implicating message, (5) indirectly characterizing characters, and (6) creating ambiguous setting.